2012
DOI: 10.1186/1752-153x-6-96
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of lycorine derivatives as dual inhibitors of humanacetylcholinesterase and butyrylcholinesterase

Abstract: BackgroundAlzheimer’s disease (AD) is a neurologically degenerative disorder that affects more than 20 million people worldwide. The selective butyrylcholinesterase (BChE) inhibitors and bivalent cholinesterase (ChE) inhibitors represent new treatments for AD.FindingsA series of lycorine derivatives (1–10) were synthesized and evaluated for anti-cholinesterase activity. Result showed that the novel compound 2-O-tert-butyldimethylsilyl-1-O-(methylthio)methyllycorine (7) was a dual inhibitor of human acetylcholi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…The cell membrane integrity of the lycorine group was negatively correlated with the dose (p < 0.01). It has been verified by the previous experimental results that the sialic acid content on the tumor cell membrane was reduced, and the integrity of the tumor cell membrane was indeed regulated by the sialic acid content on the tumor cell membrane [28].…”
Section: Antitumor Mechanism Of Lycorine On Liver Cancer Cellssupporting
confidence: 75%
“…The cell membrane integrity of the lycorine group was negatively correlated with the dose (p < 0.01). It has been verified by the previous experimental results that the sialic acid content on the tumor cell membrane was reduced, and the integrity of the tumor cell membrane was indeed regulated by the sialic acid content on the tumor cell membrane [28].…”
Section: Antitumor Mechanism Of Lycorine On Liver Cancer Cellssupporting
confidence: 75%
“…Lycorine series of Amaryllidaceae alkaloids require a hydrogen-bond acceptor at the C-1 for acetylcholinesterase and butyrylcholinesterase inhibitory activity and the lipophilic substituent at C-2 increases the activity. However, oxidation at C2 is supposed to deactivate the compound of its inhibitory effect [131,132]. The common structural Inactive [23] characteristics need for the pharmacologic activity of lycorine derivatives include, the planarity of the molecule, basic nitrogen, and free hydroxyl group.…”
Section: Structural Features Required For Anti-tumor Activity Of Lycomentioning
confidence: 99%
“…However, modification of the lycorine skeleton by acetylation may increase the inhibitory potency (1‐ O ‐acetyllycorine, IC 50 = 0.96 μ m ) . The hydrogen‐bond acceptor at the C1 of lycorine is needed for AChE inhibition, while a lipophilic substituent at C2 increases the inhibitory activity . A recent work involving lycorine derivatives showed that acylation or etherification of lycorine produces compounds able to inhibit both human BuChE (IC 50 = 4–20 μ m ) and AChE (IC 50 = 11–50 μ m ) …”
Section: Alkaloidsmentioning
confidence: 99%
“…[96] The hydrogen-bond acceptor at the C1 of lycorine is needed for AChE inhibition, while a lipophilic substituent at C2 increases the inhibitory activity. [97] A recent work involving lycorine derivatives showed that acylation or etherification of lycorine produces compounds able to inhibit both human BuChE (IC50 = 4-20 mm) and AChE (IC50 = 11-50 mm). [97] Other groups of alkaloids have been studied, but without great anti-ChE activity as compared with those mentioned above.…”
Section: Xanthonesmentioning
confidence: 99%
See 1 more Smart Citation